Postharvest parameters of the Fuerte avocado when refrigerated in different modified atmospheres - Russo, Viviane Citadini [UNESP]; Daiuto, Erica Regina [UNESP]; Vietes, Rogerio Lopes [UNESP]; Smith, Robert E. (Wiley-Blackwell, 2014)
The objective of this work was to evaluate the refrigerated "Fuerte" avocados stored in different modified active atmospheres. The fruits were wrapped in bags made of nylon plus polyethylene and submitted to the following atmospheres: (I) mixture of ambient gases (0.03% CO2 and 21.0% O-2); (II) 5.0% CO2 and 4.0% O-2; (III) 6.0% CO2 and 4.0% O-2; (IV) 7.0% CO2 and 4.0% O-2; and (V) 8.0% CO2 and 4.0% O-2. The bags containing the fruits were stored at 10C +/- 1 and 90 +/- 5% relative humidity for 25 days and were analyzed every 5 days for weight loss, respiratory activity, pH, firmness, titratable acidity, soluble solids, and activities of the enzymes pectin methylesterase and polygalacturonase. The atmosphere of 7.0% CO2 and 4.0% O-2 was the most effective in limiting the weight loss and the production of CO2.